Optimization of Thermal, Mechanical, Biodegradation, and Shape Memory Properties in 4D-Printed PLA/PCL Blends for Spinal Cages - Eryildiz, Meltem; Karakus, Aleyna; Demirci, Mehmet; Kadirhan, Ozge Altintas; Altan, Mihrigul Eksi (WILEY, 2025)
Spinal fusion cages play a crucial role in stabilizing the spine and promoting bone growth in degenerative spine disorders. Recent advancements in biodegradable polymer-based cages have introduced materials with shape memory properties, enabling minimally invasive implantation and improved adaptability. This study focuses on the development of 4D-printed PLA/PCL blend spinal cages, investigating their thermal, mechanical, biodegradation, and shape memory properties, alongside surface wettability through contact angle measurements. The novelty of this study lies in identifying the optimal PLA/PCL ratio, balancing mechanical strength, biodegradability, and shape memory behavior for spinal fusion applications. The findings highlight PLA/PCL (80:20) as the most suitable composition, offering a well-balanced combination of properties. Differential scanning calorimetry (DSC) analysis revealed that 20 wt% PCL enhances toughness, flexibility, and crystallinity while slightly reducing the glass transition temperature. Mechanical testing showed improved fracture behavior and elongation at this ratio, with tensile stress peaking before decreasing at higher PCL concentrations due to increased ductility. Biodegradation studies confirmed an increasing degradation rate with higher PCL content, while contact angle measurements indicated greater hydrophilicity, though this trend reversed at higher concentrations. Shape memory analysis demonstrated that as PCL content increased from 10 to 60 wt%, shape recovery decreased from 76.07% to 61.28%, while high shape fixity (96.42%-99.80%) was maintained. The PLA/PCL20 blend exhibited a 74.5% shape memory effect and a 68.75% recovery rate in the spinal cage design, making it a promising material for minimally invasive spinal fusion applications.
Keywords: 4D printing; biodegradation; PLA/PCL blends; shape memory properties; spinal cages; POLY(LACTIC ACID); POLYMERS; GLASS; POLY(EPSILON-CAPROLACTONE); DEGRADATION; TRANSITION; Polymer Science